2014
DOI: 10.1007/s12028-014-0003-y
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Optic Nerve Sheath Diameter and Mortality in Patients with Severe Traumatic Brain Injury

Abstract: In patients with TBI, ONSD measured on CT scanning was independently associated with ICP and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 32 publications
0
45
0
3
Order By: Relevance
“…Overall, the cohort had a mean age of 35 years and 171 of 220 were male. The median admission GCS was 6 (Sekhon et al, 2014). The correlation between ONSD and mortality was further supported by another study where the enlargement of ONSD on initial CT scan has been found to be associated with increased mortality after severe TBI.…”
Section: Traumatic Optic Neuropathymentioning
confidence: 99%
“…Overall, the cohort had a mean age of 35 years and 171 of 220 were male. The median admission GCS was 6 (Sekhon et al, 2014). The correlation between ONSD and mortality was further supported by another study where the enlargement of ONSD on initial CT scan has been found to be associated with increased mortality after severe TBI.…”
Section: Traumatic Optic Neuropathymentioning
confidence: 99%
“…Noninvasive devices do not reliably quantify ICP [46]. However, they may be used to estimate ICP when invasive monitoring is not feasible, along with information from imaging [47][48][49]. It remains a mandatory prerequisite, exploring the volume relationship inside the skull, when other intracranial monitors, exploring other domains, are used to provide a framework for optimal interpretation (Fig.…”
Section: Intracranial and Cerebral Perfusion Pressure Monitoringmentioning
confidence: 99%
“…ONSD has been shown to correlate with ICP and with outcome in the setting of traumatic brain injury (TBI). 9,10 In TBI, ICP monitoring as a means to guide therapy is the standard of care, and the ONSD may be a useful surrogate. 11 Whereas the role of ICP monitoring in TBI is well established, its role in HIBI is less clear.…”
Section: Introductionmentioning
confidence: 99%